Does exclusion of the ESR from JADAS affect validity in the clinical setting?. (24th May 2012) - McErlane, F; Beresford, MW; Baildam, EM; Thomson, W; Hyrich, K; Chieng, A; Davidson, J; Foster, HE; Gardner-Medwin, J; Lunt, M; Wedderburn, L
Abstract : Aims: Juvenile Arthritis Disease Activity Score (JADAS) is a 4 variable composite disease activity (DAS) score for JIA (including active 10, 27 or 71 joint count (AJC), physician global (PGA), parent/child global (PGE) and ESR). ESR is not routinely measured in UK clinical practice, hampering clinical feasibility of JADAS. We aim to determine whether exclusion of the ESR from JADAS (labelled JADAS-3) impacts on correlation with single markers of DA in clinical practice, through application to a prospective inception cohort of UK children presenting with new onset inflammatory arthritis. Methods: JADAS 10, 27 and 71 and JADAS-3 10, 27 and 71 were determined for all children in the Childhood Arthritis Prospective Study (CAPS) with complete data available. Correlation of JADAS and JADAS-3 with single markers of DA was determined for the whole cohort and individual ILAR subtypes using Spearman's rank statistic. Results: 262/1238 visits had sufficient data for calculation of JADAS (1028 (83%) AJC, 744 (60%) PGA, 843 (68%) PGE and 459 (37%) ESR). Median age at disease onset was 6.0 years (IQR 2.6-10.4) and 64% were female. Correlation of JADAS and JADAS-3 was high, both for the whole cohort (0.82) and within individual ILAR subtypes. With the exception of the ESR, correlations of JADAS and JADAS-3 with single DA markers were similar; both for the whole cohort and within the ILAR subtypes (AJC JADAS 0.59 JADAS3 0.73, PGA JADAS 0.64 JADAS3 0.75, PGE JADAS 0.61 JADAS3 0.75, ESR JADAS 0.53, JADAS3 0.07, limited JC JADAS 0.41 JADAS3 0.48, Parental pain JADAS 0.53 JADAS3 0.61, CHAQ JADAS 0.47 JADAS3 0.56). Conclusion: Correlation with single DA markers was very similar for JADAS and JADAS-3, both in the group overall and within the ILAR subtypes. Correlation of JADAS-3 with the ESR was low but correlation with all other surrogates for DA was at least as high as JADAS. JADAS-3 may be a valid surrogate for DA in the clinical setting when the ESR is unavailable. Further validation is required to determine whether JADAS and JADAS-3 reflect changes in DA over time.